Urgensi Sekolah Organisasi dalam Membentuk Jiwa Kepemimpinan Berintegritas di PP. Annuqayah Latee Sumenep - syaiful, ipung (Trunojoyo University of Madura, 2024)
Leaders had very central role in an organization. How fast an organization can run well depends on the quality, capacity and credibility of the leader. However, it becomes odourless when the leader is not accompanied by a strong mandate of integrity so that it implies against the emergence of violations of normative or constitutional nature. That's why the trainer is here to answer the question. Despite the taboos of the organizational world, the trainees made special formulations such as setting up an organizational school as an initial policy. This article aims to reveal the urgency of organizing schools in the boarding houses in giving birth to the soul of integrated leadership. A study at PP. Annuqayah Latee Sumenep. This descriptive-qualitative research is obtained from the results of interviews with several lecturer managers, organizing committees as well as activities participants as a primary source, while secondary data is derived from examination of some of the library materials relating to the research themes that we raised. From it can be concluded that the school of organizations has its own urgency in giving birth to the spirit of integrated leadership, such as: the cultivation of the character of a leader and integrity, decision-making techniques, monitoring and construction, as well as presenting an exemplary